Country image and branding of Slovakia - Katarína Kleinová; Johana Űrgeová (Polityki Europejskie, Finanse i Marketing)
The paper points at some points of country marketing, for example how European countries could be successful in the situation of global competitiveness, not only taking into account their history or culture but also in the area of product image, such as a country of origin. Country in its own is also a way of a brand. Most countries communicate with the rest of the world on several levels and so they create their images whether knowingly or randomly. Political decisions of the government, the ways of attracting foreign investors and skilled workforce, export of products, export of culture, promotion of tourism and ultimately inhabitants themselves of the country are also either positively or negatively involved in creating the country image.